2010
DOI: 10.3390/cancers2020498
|View full text |Cite
|
Sign up to set email alerts
|

Possible DNA Viral Factors of Human Breast Cancer

Abstract: Viruses are considered to be one of the high-risk factors closely related to human breast cancer. However, different studies of viruses in breast cancer present conflicting results and some of these works remain in dispute. DNA viruses, such as specific types of human papillomaviruses (HPV), Epstein–Barr virus (EBV), human cytomegalovirus (HCMV), herpes simplex virus (HSV), and human herpes virus type 8 (HHV-8), have emerged as causal factors of some human cancers. These respective exogenous viruses and the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 81 publications
0
30
0
Order By: Relevance
“…Although the presence of a virus alone does not establish a causal role in the disease and other techniques are not used to prove the attendance of EBV-DNA in tumor cells, our findings with 9.3% positivity, in addition to the previously reported positive results, supports the possibility of an etiologic relationship. The proof of etiologic role of EBV in the induction of breast carcinoma needs more efforts using more specific and sensitive techniques (1,2,16,17). If the association of one or more of these viruses with breast cancer can be established, there is a possibility of prevention by anti-viral treatments and vaccination strategies (11).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the presence of a virus alone does not establish a causal role in the disease and other techniques are not used to prove the attendance of EBV-DNA in tumor cells, our findings with 9.3% positivity, in addition to the previously reported positive results, supports the possibility of an etiologic relationship. The proof of etiologic role of EBV in the induction of breast carcinoma needs more efforts using more specific and sensitive techniques (1,2,16,17). If the association of one or more of these viruses with breast cancer can be established, there is a possibility of prevention by anti-viral treatments and vaccination strategies (11).…”
Section: Resultsmentioning
confidence: 99%
“…The review article by Hsu et al (1) reported that HPV, EBV, CMV, HSV-1, and HHV-8 may be contributing to breast cancer. The study by Lawson and colleagues (4) suggested the association between EBV and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has led to studies to identify new factors related to this neoplasia1456. Infectious agents have been implicated, as either direct carcinogens or promoters.…”
mentioning
confidence: 99%